Transition of Son Preference: Evidence From South Korea. - Choi, Eleanor Jawon; Hwang, Jisoo (Demography (Springer Nature), 2020)
Sex ratio at birth remains highly skewed in many Asian countries because of son preference. The ratio in South Korea, however, declined beginning in 1990 and reached the natural range in 2007. We study changes in child gender effects on fertility and parental investment during this period of decreasing sex ratio at birth. We find that gender discrimination on the extensive margin (fertility), such as sex-selective abortions and son-biased stopping rules, have nearly disappeared among recent cohorts. On the intensive margin (parental inputs), boys receive higher expenditures on private academic education, have mothers with fewer hours of labor supply, and spend less time on household chores relative to girls. These gender gaps have also narrowed substantially, however, over the past two decades. We consider alternative explanations, but altogether, evidence suggests the weakening of son preference in South Korea.